Impulse Buying Behavior Santri Perspektif Maslahah Imam Al-Ghazali - Aula Izatul Aini; Aushofun Niha (IAI Darussalam, 2020)
The purpose of this research is, first, to determine the impulse buying behavior on the behavior of students university at the Darussalam Islamic Boarding School Blockagung Banyuwangi. Second, to find out the impulse buying behavior of students at university at the Darussalam Boarding School Blokagung Banyuwangi in terms of the perspective of Imam Al-Ghazali's maslahah. Research using qualitative methods with the type of phenomenological research. The data source uses primary data and secondary data. The data analysis technique used is interactive models. The results of his research are impulse buying behavior by students at university at the Darussalam Islamic Boarding School Blokagung Banyuwangi Regency balanced between purchases based on needs and desires. However, the impulsive buying behavior of students at university has not fully carried out the purchase in accordance with Imam Al-Ghazali’s maslahah. Although the results of the study state that there is a balance between buying based on need and desire, in making a purchase there is still no review of the five aspects of maqashid as-shari'ah or usulul khomsah. In addition, purchases made as a desire to satisfy will only lead to wasteful and wasting money